(untitled) (Hematology Meeting Reports, 2009)
One of the most exciting issue related to anticoagulant therapy is its potential for an antineoplastic effect. The notion that anticoagulants have an antineoplastic effect is provocative. A strong association between cancer and thrombosis has been demonstrated consistently in experimental and clinical studies. Randomized controlled trials and meta-analyses of studies that compared low molecular weight heparins (LMWH) with unfractionated heparin for the initial treatment of venous thromboembolism have reported a reduction in the overall mortality of patients with cancer who were randomly assigned to receive a LMWH.1